2020
DOI: 10.3171/2020.6.focus20393
|View full text |Cite
|
Sign up to set email alerts
|

Does interbody cage lordosis impact actual segmental lordosis achieved in minimally invasive lumbar spine fusion?

Abstract: OBJECTIVEIn an effort to prevent loss of segmental lordosis (SL) with minimally invasive interbody fusions, manufacturers have increased the amount of lordosis that is built into interbody cages. However, the relationship between cage lordotic angle and actual SL achieved intraoperatively remains unclear. The purpose of this study was to determine if the lordotic angle manufactured into an interbody cage impacts the change in SL during minimally invasive surgery (MIS) for lumbar interbody fusion (LIF) done for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…This is in line with Carlson, et al 31 who reported that an anterior position of the cage resulted in larger postoperative SL. Lovecchio, et al 19 also reported that SL increased more following ALIF than after TLIF or LLIF, and they thus concluded that cage position was the only factor influencing SL change after MIS-TLIF. We also found that the Yc axis of the cage was associated with SL, with an anterior cage position correlating with an increase in SL after MIS-TLIF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is in line with Carlson, et al 31 who reported that an anterior position of the cage resulted in larger postoperative SL. Lovecchio, et al 19 also reported that SL increased more following ALIF than after TLIF or LLIF, and they thus concluded that cage position was the only factor influencing SL change after MIS-TLIF. We also found that the Yc axis of the cage was associated with SL, with an anterior cage position correlating with an increase in SL after MIS-TLIF.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have reported a relationship between cage characteristics and lordosis. 12 13 14 15 16 17 18 19 20 21 22 However, how cage position affects postoperative lordosis after MIS-TLIF has only been studied indirectly by comparing dichotomized groups of anterior or posterior cage positioning. 14 19 In this study, we sought to identify factors that may affect segmental lordosis (SL) after MIS-TLIF by comparing patients whose SL increased with those whose decrease.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these changes were statistically significant. At the rear of the neck, the lumbar spine is fused [ 7 ].…”
Section: The Following Issues May Arise Because Of Missmentioning
confidence: 99%
“…The anatomical factors like unilateral facetectomy and lack of anterior release in MIS TLIF limited the segmental sagittal lordosis. 36 Champagne et al 37 retrospectively compared the sagittal balance correction in 148 patients with open TLIF, MIS TLIF and OLIF and found that pelvic incidence and pelvic tilt remained the same in all and only OLIF could significantly increase the segmental lordosis. The lumbar lordosis was significantly improved only with OLIF and not with MIS TLIF.…”
Section: Sagittal Deformity and Mis-tlifmentioning
confidence: 99%